INTEGRATED ASSESSMENT OF GEOMORPHOLOGICAL AND STRATIGRAPHIC GEOLOGICAL MONUMENTS VOLYN – PODOLIA - Bondar, Yu. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The evaluation of geomorphological and stratigraphic geological monuments Volyn-Podolia is examined out using the techniques of geological and economic analysis. It was developed evaluation criteria and indicators of geological and economic evaluation of geological monuments and place ranking for the selection of the most promising for further development. It was defined that Verteba cave, Ozerna cave, Optymistychna cave, Crystal cave and Canyon of Seret River in Kasperivtsi village are characterized by maximal favorable characteristics.